Fourier-transform spectroscopy and relativistic electronic structure calculation on the c3Σ+ state of KCs. (December 2021) - Kruzins, A.; Krumins, V.; Tamanis, M.; Ferber, R.; Oleynichenko, A.V.; Zaitsevskii, A.; Pazyuk, E.A.; Stolyarov, A.V.
Highlights: 673 experimental term values belonging to both e / f -components of the c 3 Σ Ω = 1 + state of KCs were determined with about 0.01 cm − 1 accuracy applying high resolution Fouriertransform spectroscopy. High fidelity relativistic coupled cluster calculation on the electronic structure of the KCs low-lying states was performed. Semi-empirical point-wise interatomic potential was reconstructed for the c 3 Σ 1 + state. Ω -doubling effect in the c 3 Σ 1 + state was investigated. Radiative properties of the c 3 Σ + state were simulated for the lowest vibrational v c ≤ 22 levels. Abstract: The Ti:Saphire laser operated within 13800 - 11800 cm − 1 range was used to excite the c 3 Σ + state of KCs molecule directly from the ground X 1 Σ + state. The laser-induced fluorescence (LIF) spectra of the c 3 Σ + → a 3 Σ + transition were recorded with Fourier-transform spectrometer within 8000 to 10000 cm − 1 range. Overall 673 rovibronic term values belonging to both e / f -components of the c 3 Σ + ( Ω = 1 ± ) state of 39 KCs, covering vibrational levels from v = 0 to about 45, and rotational levels J ∈ [ 11, 149 ] were determined with the accuracy of about 0.01 cm − 1 ; among them 7 values for 41 KCs. The experimental term values with v ∈ [ 0, 22 ] were involved in a direct point-wise potential reconstruction for the c 3 Σ + ( Ω = 1 ± ) state, which takes into account the Ω -doubling effect caused by the spin-rotational interaction with the nearby c 3 Σ + ( Ω = 0 − ) state. The analysis and interpretation were facilitated by the fully-relativistic coupled cluster calculation of the potential energy curves for the B 1 Π, c 3 Σ +, and b 3 Π states, as well as of spin-forbidden c − X and spin-allowed c − a transition dipole moments; radiative lifetimes and vibronic branching ratios were calculated. A comparison of relative intensity distributions measured in vibrational c → a LIF progressions with their theoretical counterparts unambiguously confirms the vibrational assignment suggested in [ J. Szczepkowski, et al., JQSRT, 204, 133–137 (2018)].